Effect of different separated nickel-titanium rotary instruments on apical microleakage: An in vitro study - Roohollah Sharifi; Ehsan Heidarzadi; Ehsan Azizi; Abbasali Khademi; Saber Khazaei; Pedram Iranmanesh (Wolters Kluwer Medknow Publications, 2022)
Introduction: Endodontic instrument separation is one of the iatrogenic errors which may affect the outcome of treatment. The present in vitro study was aimed to investigate the effect of different cross-sectional designs of separated nickel-titanium (Ni-Ti) rotary files on apical microleakage. Materials and Methods: A total of 48 mandibular premolar roots were selected. The samples were randomly assigned to four experimental groups including Mtwo (n = 10), HERO Shaper (n = 10), RaCe (n = 10), and FlexMaster (n = 10) as well as positive (n = 4) and negative (n = 4) control groups. Ni-Ti rotary instruments with the same size and taper (0.06, #30) were separated in the apical region after complete cleaning and shaping, and the remaining root canal was obturated with gutta-percha and AH-26 sealer. The bacterial microleakage of each group was assessed through Enterococcus faecalis for 60 days. Survival analysis was done by SPSS 22. Results: There were no statistically significant differences between the studied groups in terms of the time of microleakage (P = 0.955). Conclusion: The separated Ni-Ti rotary instruments with different cross-sectional designs had no impact on apical microleakage.